Construction and validation of a spatial database of providers of transgender hormone therapy in the US. (June 2022) - Everhart, Avery R.; Ferguson, Laura; Wilson, John P.
Abstract: What little data on transgender healthcare is available often focuses on transgender people's negative experiences in accessing healthcare. However, no research has been conducted that illustrates where gender-affirming hormone therapy, one part of transgender-specific medical care, is available. Without these data, large scale research to discern patterns of availability of and access to gender-affirming medical care is nearly impossible. Community-based organizations, and even trans individuals themselves have constructed repositories and databases of healthcare providers to inform other care seekers where they can access transition-related care providers, but their data are often incomplete, and usually formatted to be user-facing rather than streamlined for research purposes. To fill this gap, this article outlines the methodology for the construction of a spatial database of providers of gender-affirming hormone therapy for transgender people in the US, which is available on GitHub, created from existing community-based resources and the accompanying verification process. The completeness of the database is tested via comparison to data from the US Transgender Survey in which respondents reported travel distance to access transgender-specific care providers. The database accounted for all but 7.5% of respondents who may have accessed unknown facilities based on self-reported travel distance. Results indicate that existing methodologies for database construction regarding healthcare providers are difficult to apply when working with transgender-specific medical care and that tests for replicability and validation often take for granted the wide availability of relevant data and information. While the database unto itself can only demonstrate where care is available, it will enable future research into why these geographic patterns in care availability exist. Finally, the methodology can be replicated to produce databases for other kinds of specialized or politicized medical care such as abortion, gender-affirming surgery, or HIV treatment. Highlights: The geographic availability of transgender medical care remains understudied. Our spatial database of GAHT providers drew on community resources to fill this gap. We validated it via public information and a test of efficacy using USTS data. We identified 92.5% of possible facilities according to reported travel distance. Our mixed-methods approach could be replicated for other kinds of politicized care.